2008
DOI: 10.1007/s00534-007-1240-7
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative evaluation of pancreatic adenocarcinoma

Abstract: The preoperative evaluation of resectability for pancreatic cancer fails to identify up to 25% of patients who are unfortunately found to be unresectable at surgical exploration. Inoperative findings in this circumstance is usually due to either small volume metastatic disease or regional tumor invasion. While advances in computed tomography (CT) technology has increased accuracy of local tumor extent, occult metastatic disease remains a common problem. Although 2-[(18)F]fluoro-2-deoxy-D-glucose positron emiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 68 publications
1
43
0
1
Order By: Relevance
“…However, surgery is not an option for patients who initially present with locally advanced (AJCC stage III) disease and who have a reported median survival period of less than 12 months (35). Therefore, in clinical practice, stage-specific treatment of pancreatic adenocarcinoma is based on whether a tumor is potentially resectable, locally advanced or metastatic, and, therefore, the fundamental question in the initial staging evaluation of pancreatic adenocarcinoma is the determination of resectability (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, surgery is not an option for patients who initially present with locally advanced (AJCC stage III) disease and who have a reported median survival period of less than 12 months (35). Therefore, in clinical practice, stage-specific treatment of pancreatic adenocarcinoma is based on whether a tumor is potentially resectable, locally advanced or metastatic, and, therefore, the fundamental question in the initial staging evaluation of pancreatic adenocarcinoma is the determination of resectability (15).…”
Section: Discussionmentioning
confidence: 99%
“…One reason for this is the decreased specificity for resectability caused by unexpected small (Ͻ 1 cm in diameter) liver metastasis (n ϭ 2) which was not even detected on retrospective review of the images. Although the superiority of contrast-enhanced MR over CT for detecting hepatic metastasis has already been previously reported, it can be further improved with the use of liver specific MR contrast media (especially with hepatobiliary agents) (11,23), although unexpected hepatic metastasis is still problematic in clinical practice (15). Studies of mangafodipir trisodium-enhanced MR imaging have shown improved tumor delineation and diagnostic confidence as well as improved detection of small (Ͻ 2 cm) liver metastasis compared with singledetector helical CT (11,26,42).…”
Section: Discussionmentioning
confidence: 99%
“…De acordo com várias publicações, a tomografia de abdome com múltiplos detectores é na atualidade o exame preferido para o diagnóstico e estadiamento do AP 2,6,30,34,35 . Ela permite exame rápido em um único evento de apnéia, com fases arterial, portal e parenquimatosa, com cortes finos e reconstrução em vários planos.…”
Section: Estadiamento Exames Pré-operatóriosunclassified
“…[1,2] Despite the potency and versatility of 18 F-labeled 2-deoxy-2-fluoro-D-glucose ( 18 F-FDG) in diagnosis/staging of various tumor types, it is not a sufficiently useful tool for the staging of this particular cancer. [3] Therefore, the development of a new non-invasive and accurate method for preoperative staging of pancreatic carcinoma is necessary. It has been shown that more than 75% of ductal pancreatic adenocarcinomas overexpress neurotensin (NT) receptors.…”
Section: Introductionmentioning
confidence: 99%
“…In this article, we describe the radiochemical and biological evaluation of a new radiolabeled NT analogue (5)(6)(7)(8)(9)(10)(11)(12)(13) Tc. This is significant because the radiolabeling of NT analogues with 99m Tc was mainly reported using the tricarbonyl approach and several new radiolabeled NT analogues with 99m Tc through bifunctional chelating agents such as MAG 3 , N 4 , and HYNIC. We should consider various limitations in previous studies such as the labeling procedure and the biological behavior for example, in the 99m Tc-carbonyl approach, consideration of the two-step preparation and further purification of the final product, the lack of studies in the tumor model in radiolabeling via MAG 3 , low tumor uptake, and low internalization via HYNIC make them unsuitable for utilization in nuclear medicine.…”
Section: Introductionmentioning
confidence: 99%